Optimization of Antibacterial, Structures, and Thermal Properties of Alginate-ZrO2 Bionanocomposite by the Taguchi Method - Mohsen Safaei; Hedaiat Moradpoor; Mohammad Salmani Mobarakeh; Nima Fallahnia (Journal of Nanotechnology)
Developing novel antibacterial chemicals is constantly necessary since bacterial resistance to antibiotics is an inevitable occurrence. This research aimed to find the ideal conditions for using antibacterial zirconia (ZrO2) NPs with polymer alginate nanocomposites. Using the Taguchi method, alginate biopolymer, zirconia NPs, and stirring time were utilized to construct nine nanocomposites. Analysis of Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible (UV-vis), spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), and thermogravimetric analysis (TGA) indicated the development of nanocomposites with appropriate structural properties. Antibacterial efficacy against Streptococcus mutans (S. mutans) biofilm was the highest when the nanocomposite was formed under the circumstances of experiment 6 (zirconia 8 mg/ml, alginate 70 mg/ml, and 40 min stirring time). Alginate/zirconia bionanocomposites generated using the in situ technique proved efficient against S. mutans. Nanoparticles have a high surface-to-volume ratio and surface energy, which can cause them to agglomerate and make their antimicrobial effectiveness problematic. Using zirconia nanoparticles in an alginate polymer matrix in the form of nanocomposite can increase the stability of nanoparticles. Due to the advantageous antibacterial qualities of this bionanocomposite, it can be utilized in various medical materials and dental appliances.